2019
DOI: 10.1101/669036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying conserved molecular targets required for cell migration of glioblastoma cancer stem cells

Abstract: Glioblastoma (GBM) is the most prevalent primary malignant brain tumor and is associated with extensive tumor cell infiltration into the adjacent brain parenchyma. However, there are limited targeted therapies that address this disease hallmark. While the invasive capacity of self-renewing cancer stem cells (CSCs) and their non-CSC progeny has been investigated, the mode(s) of migration used by CSCs during invasion is currently unknown. Here we used time-lapse microscopy to evaluate the migratory behavior of C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…However, it remains unknown whether our modeling results pertain to a specific mode of cell motility and/or path of migration. Both individual and collective migrations have been identified in GB (Vollmann-Zwerenz et al 2020) (Volovetz et al 2020). Enrichment of oRG-like gene modules in M HIGH cells suggests that the motile cells we captured move in a solitary fashion like oRGs in the developing cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains unknown whether our modeling results pertain to a specific mode of cell motility and/or path of migration. Both individual and collective migrations have been identified in GB (Vollmann-Zwerenz et al 2020) (Volovetz et al 2020). Enrichment of oRG-like gene modules in M HIGH cells suggests that the motile cells we captured move in a solitary fashion like oRGs in the developing cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Three major migration/invasion routes have been described: the narrow and tortuous extracellular space of the brain parenchyma (Scherer 1938), the perivascular spaces surrounding blood vessels (Scherer 1938) (Montana & Sontheimer 2011) (Watkins et al 2014) (Cuddapah et al 2014) and white matter tracts, notably the corpus callosum, used as a highway for bilateral brain hemisphere invasion (Scherer 1938) (Pedersen et al 1995). Both single cell and collective migration have been reported (Vollmann-Zwerenz et al 2020) (Volovetz et al 2020), the latter appearing to be facilitated by the formation of an interconnected network of tumor microtubes (Osswald et al 2015). So far, an integrated view of the metabolic pathways at play in a motile GB cell is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this 10% difference may be attributed to the presence of a CSC population in WK1 cells, which is less susceptible to treatment with Tf@pSiNPs (Fig. 6) and is established as being more invasive than non-CSCs [45][46][47][48]. For example, Volovetz et al [46] found that glioma stem cells showed 2-5 times greater cell motility when compared to non-CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…6) and is established as being more invasive than non-CSCs [45][46][47][48]. For example, Volovetz et al [46] found that glioma stem cells showed 2-5 times greater cell motility when compared to non-CSCs. Our observation is further consolidated by previous investigations showing that on average glioma stem cells constitute approximately 10-13% of primary glioma cells [26,49,50].…”
Section: Discussionmentioning
confidence: 99%